The Effectiveness of Bibliotherapy and Group Counseling in Reducing the Level of Psychological Loneliness among Non Jordanian Students at Yarmouk University - Al-Shraifin , Ahmad; Al-Mifleh, Eman (Jordan Journal of Educational Sciences, 2014)
The aim of this study was to investigate the effectiveness of bibliotherapy and group counseling in reducing the level of psychological loneliness among non Jordanian students. The study sample consisted of (45) non-Jordanian male and female students who came from (19) Arabic countries, spoke Arabic Language and studied at Yarmouk University during 2012/2013. The students were randomly assigned to either one of two experimental groups or a control group. The first one of the experimental group was provided with a manual for reducing the level of psychological loneliness designed by the researchers (Bibliotherapy), whereas the second group was provided with the counseling psychology program designed by the researchers. The control group wasn’t provide with any intervention. The result of the study revealed that there were statistical significant differences due to the group (Treatment/Therapy method: bibliotherapy, group counseling and control group) for control group which had the higher level of loneliness, and there were statistical significant differences due to the interaction between group and gender; males in control and first group had a higher level of loneliness, while females in second group had a higher level of loneliness than males. The result also revealed that there are no statistically significant differences in the overall scale due to gender. The study recommended executing and applying the two psychological programs on expatriate students to enhance psychological health and needing more research to examine the effectiveness of cognitive programs and behavioral programs in reducing the level of psychological loneliness among students